The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s00213-003-1450-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bupropion on nicotine self-administration in rats

Abstract: These results suggest that high bupropion doses decrease responding nonspecifically; whereas low bupropion doses selectively increase responding for nicotine. The increase in nicotine self-administration is likely due to inhibition of dopamine and norepinephrine transporters, combined with inhibition of nAChRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 29 publications
(51 reference statements)
9
108
2
Order By: Relevance
“…However, since there were no differences in the effect of pretreatment with 10 mg/kg of methylphenidate between rats self-administering either nicotine unit dose, it is possible that high doses of stimulants can alter nicotine self-administration nonspecifically. While the precise reason(s) for this biphasic pattern of results is unknown, Rauhut et al (2003) found similar biphasic dose effects of acute bupropion or methamphetamine pretreatment on nicotine self-administration in rats. Prada and Goldberg (1985) also reported that caffeine pretreatment increased nicotine self-administration in squirrel monkeys at low doses (3-10 mg/kg), while higher doses (60-100 mg/kg) decreased response rates.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, since there were no differences in the effect of pretreatment with 10 mg/kg of methylphenidate between rats self-administering either nicotine unit dose, it is possible that high doses of stimulants can alter nicotine self-administration nonspecifically. While the precise reason(s) for this biphasic pattern of results is unknown, Rauhut et al (2003) found similar biphasic dose effects of acute bupropion or methamphetamine pretreatment on nicotine self-administration in rats. Prada and Goldberg (1985) also reported that caffeine pretreatment increased nicotine self-administration in squirrel monkeys at low doses (3-10 mg/kg), while higher doses (60-100 mg/kg) decreased response rates.…”
Section: Discussionmentioning
confidence: 78%
“…As these mechanisms would suggest, it has been shown that coadministration of methylphenidate augments nicotineinduced increases in extracellular dopamine content in the NAcc (Gerasimov et al, 2000a, b), suggesting that the interactive effects of these drugs on mesolimbic dopamine transmission underlies the behavioral interactions noted in the present study. Regarding self-administration specifically, blockade of central dopamine receptors reduces nicotine self-administration (Corrigall and Coen, 1991;Corrigall et al, 1992), whereas administration of monoamine oxidase inhibitors or the dopamine reuptake inhibitor bupropion increases nicotine self-administration (Guillem et al, 2005(Guillem et al, , 2006Rauhut et al, 2003). One caveat to this interpretation is that methylphenidate and bupropion are relatively nonselective inhibitors of the norepinephrine and dopamine transporters Han and Gu, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine attenuated reinstatement of methamphetamine self-administration (Hiranita et al, 2004;Hiranita et al, 2006), and mecamylamine decreased methamphetamine self-administration in rats (Glick et al, 2002). In rats trained to self-administer nicotine, bupropion and methamphetamine increased selfadministration of low doses of nicotine and decreased self-administration of high doses of nicotine (Rauhut et al, 2003). These findings indicate a definite interaction between the two compounds; in particular, that the two compounds produce cross-sensitization implies a similar mechanism.…”
Section: Interactions Between Methamphetamine and Nicotinementioning
confidence: 73%
“…The most obvious possibility is that nicotinic acetylcholine receptors are located on dopaminergic neurons in the ventral tegmental area which are important in regulating neuronal activity of these dopaminergic neurons (Mameli-Engvall et al, 2006;Ungless and Cragg, 2006). Administration of nicotine modulates dopamine release (Quarta et al, 2006;Wonnacott et al, 2005), and is known to alter behaviors controlled by these dopaminergic pathways including locomotor behavior (Kuribara, 1999;Suemaru et al, 1993) and self-administration of abused compounds, including both nicotine and methamphetamine (Glick et al, 2002;Hiranita et al, 2004;Hiranita et al, 2006;Rauhut et al, 2003). The failure of mecamylamine to block the cross-substitution of methamphetamine in nicotine-trained rats may be related to the finding that perfusion of mecamylamine into the nucleus accumbens did not alter dopamine levels in the ventral tegmental area or the nucleus accumbens (Rahman and McBride, 2002).…”
Section: Mechanismsmentioning
confidence: 99%